Production, nutritional value and recovery efficiencies and nitrogen utilization of corn silage under different doses of nitrogen fertilizer - Menezes, Luis Fernando Glasenapp de; Ronsani, Ricardo; Pavinato, Paulo Sérgio; Biesek, Ronaldo Rubens; Silva, Carlos Eduardo Kruger da; Martinello, Clederson; Cappellesso, Bruno; Silveira, Magali Floriano da (Semina: Ciências Agrárias, 2013)
The objective of this experiment was to evaluate the yield and quality of corn silage with different nitrogen levels. It was used four levels of nitrogen, 0, 80, 160, 240 kg.ha-1. The experimental design was randomized blocks with six replications. The data were subjected to analysis of variance and polynomial regression analysis. The silage was performed manually in PVC tubes of 10 cm diameter and 50 cm high. The parameters evaluated were productive variable, morphological variable, physiological efficiency, recovery efficiency and efficiency utilization of nitrogen, and nutritive value of silages. Plant height (height = 1.72+0.067*block+0.0004*N) and total production (total production = 13,883.42 + 786.41* block + 18.65*N) responded positively according increasing nitrogen dose. The decrease of recovery efficiency (NAR = 1.027-0.00283*N) and nitrogen use efficiency (NUE = 42.89 to 0.11 * N) with the increase in the amount of nitrogen applied. The crude protein of the silage shown a quadratic response (CP = 5.820+0.018*N-0.00005N2) according to the increase in nitrogen level. The increase in nitrogen levels provided better productivity with high quality silage. Higher doses showed lower nitrogen utilization efficiency and recovery nitrogen.